The de Jure 'Artist' of the Bobrinski Bucket: Production and Patronage of Metalwork in pre-Mongol Khurasan and Transoxiana - Kana'an, Ruba (Islamic law and society, 2009)
Abstract The Bobrinski bucket, made in Herat in 599/1163, is one of the most iconic metalwork objects studied by historians of Islamic art. To date, art historical scholarship on the bucket has focused on interpreting its decorative programme and identifying the decorator, Mas'ud ibn Ahmad, whose name is inscribed on the bucket, as the 'artist' who had the intellectual property of the design and its application. In this essay, I investigate the meaning of signatures left by 'artists' by examining the range of possible relationships between four men whose names appear in the dedication inscription of the Bobrinski bucket. The legal writings of Hanafī jurists from Khurasan and Transoxiana, including al-Sarakhsī (d. ca. 1090), provide an important, and hitherto unexplored, source for understanding the legal rights and responsibilities of the different parties involved in the production of a metalwork object from conception to final product, including the stages of commissioning, manufacture, sale, and repair. The treatment by Muslim jurists of the different forms of trade provides a better understanding of the potential legal and contractual capacity in which a metalwork artist could sign his work.